Causes of suicide in married women - Memari A; Ramim T; Amirmoradi F; Khosravi Kh; Godarzi Z (Tehran University of Medical Sciences, 2006)
Background & Aim: Suicide is an intentional death that occurs three time in women to men. Nurses can influence in presentation of educational program and consultation in school, job environment and home as well as detection of person who suspected to suicide. This study has conducted to determine the causes of suicide in married women. Methods & Materials: This investigation is a descriptive study that has been made among women who admitted to Loghmanoddole-Adham poisoning emergency center in Tehran, Iran (the only poisoning emergency center in Tehran) during one year (from December 2001 to December 2002). Inclusion criteria were female, married, without history of medical, mental disorders and confession to suicide. Data were collected by a questionnaire and interview and were analyzed with descriptive statistics and a chi-square test. Results: According to the result, there was statistically significant differences between age groups, living areas, educational levels, jobs and financially states. 37.4% of women had forced marry; 50.5% had feared of their husband; 67.7% had experienced husband's violence; 74.7% didn't know any supportive sources in the society. 82.8% of women used of medications (tablets) for suicide. Conclusion: This research showed that family violence and marital conflict are the most important etiology of suicide in the women. Nurses can decrease of acting to suicide in married women with detection of family violence, increasing of clients' self-esteem, referring and follow up.